Vaginal neutrophils eliminate sperm by trogocytosis. Issue 11 (4th October 2020) - Olivera-Valle, I; Latorre, M C; Calvo, M; Gaspar, B; Gómez-Oro, C; Collazos, A; Breton, A; Caballero-Campo, P; Ardoy, M; Asensio, F; Sánchez-Mateos, P; Pérez-Millan, F; et al.
Abstract: STUDY QUESTION: What is the vaginal polymorphonuclear (PMN) spermicidal mechanism to reduce the excess of sperm? SUMMARY ANSWER: We show that PMNs are very efficient at killing sperm by a trogocytosis-dependent spermicidal activity independent of neutrophil extracellular traps (NETs). WHAT IS KNOWN ALREADY: Trogocytosis has been described as an active membrane exchange between immune cells with a regulatory purpose. Recently, trogocytosis has been reported as a mechanism which PMNs use to kill tumour cells or Trichomonas vaginalis . STUDY DESIGN, SIZE, DURATION: We used in vivo murine models and human ex vivo sperm and PMNs to investigate the early PMN–sperm response. PARTICIPANTS/MATERIALS, SETTING, METHODS: We set up a live/dead sperm detection system in the presence of PMNs to investigate in vivo and ex vivo PMN-spermicidal activity by confocal microscopy, flow cytometry and computer-assisted sperm analysis (SCA). MAIN RESULTS AND THE ROLE OF CHANCE: We revealed that PMNs are highly efficient at killing sperm by way of a NETs-independent, contact-dependent and serine proteases-dependent engulfment mechanism. PMNs 'bite' sperm and quickly reduce sperm motility (within 5 min) and viability (within 20 min) after contact. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: This study was conducted using murine models and healthy human blood PMNs; whether it is relevant to human vaginal PMNs or to cases of infertility is unknown. WIDER IMPLICATIONS OF THE FINDINGS: Vaginal PMNs attack and immobilize excess sperm in the vagina by trogocytosis because sperm are exogenous and may carry pathogens. Furthermore, this mechanism of sperm regulation has low mucosal impact and avoids an exacerbated inflammatory response that could lead to mucosal damage or infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was partially supported by Ministry of Economy and Competitiveness ISCIII-FIS grants, PI16/00050, and PI19/00078, co-financed by ERDF (FEDER) Funds from the European Commission, 'A way of making Europe' and IiSGM intramural grant II-PI-MRC-2017. M.R. holds a Miguel Servet II contract (CPII14/00009). M.C.L. holds IiSGM intramural contract. There are no competing interests.